Positive sentinel lymph node in melanoma: predictive factors and results of completion lymph node dissection (Revista Argentina de Cirugía, 2026)
Background: Sentinel lymph node (SLN) biopsy is the technique accepted to determine the prognosis of early cutaneous melanomas. The advantage of lymph node dissection (LND) when SLN biopsy is positive has recently been questioned.Objective: The aim of this study is to describe the percentages and factors associated with SLN and non-sentinel node (NSN) metastases in LNDs of SLN-positive patients.Material and methods: The clinical records and pathology reports of 139 patients undergoing surgery for cutaneous melanoma between January 2012 and December 2019 were retrospectively reviewed.Results: Ninety-six (69%) patients underwent SLN biopsy. Mean age was 61.7 ± 17.5 years (19-93) and 53 (55.2%) were men. The primary lesion was located in the extremities in 47 (49%) cases, in the trunk in 39 (40.6%), and in the head and neck in 10 (10.4%). Mean Breslow thickness was 5.01 mm (1.05-50 mm) and ulceration was found in 35 cases (36.4%).The SLN was identified in all the cases and was positive in 39 (40.6%). There was an association with thickness ≥ 3 mm (p = 0.000017) and ulceration (p = 0.0011). Those patients with positive SLN biopsy underwent LND of the territory involved: axillary in 23, inguinal in 10 and cervical in 6. Twenty-three (59%) presented NSLN metastases and were associated with thickness (p = 0.022) and ulceration (p = 0.019).Conclusion: There was a high percentage of positive NSLN in the population studied which was associated with thickness and ulceration.
Keywords: melanoma; sentinel lymph node biopsy; lymph node dissection